2022
DOI: 10.1242/jeb.243175
|View full text |Cite
|
Sign up to set email alerts
|

Impact of natural and artificial prenatal stimulation on the behavioural profile of Japanese quail

Abstract: As the sensory systems of vertebrates develop prenatally, embryos perceive many environmental stimuli that can influence the ontogeny of their behaviour. Whether the nature and intensity of prenatal stimuli affect differently this ontogeny remains to be investigated. In this context, this study aimed to analyse the effects of prenatal auditory stimulations (natural stimulations “NS”: predator vocalisations, or artificial stimulations “AS”: metallic sounds) on the subsequent behaviour of young Japanese quail (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…First, it could be of value to research which aspect of transport is most stressful (e.g. noise, temperature changes, vibrations or acceleration); in ovo chronic noise exposure, for instance, has been demonstrated to affect later behaviour in young quail (Mezrai et al, 2022). Temperature, including local differences in temperature, may also be a stressor.…”
Section: Future Research and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it could be of value to research which aspect of transport is most stressful (e.g. noise, temperature changes, vibrations or acceleration); in ovo chronic noise exposure, for instance, has been demonstrated to affect later behaviour in young quail (Mezrai et al, 2022). Temperature, including local differences in temperature, may also be a stressor.…”
Section: Future Research and Recommendationsmentioning
confidence: 99%
“…Studies of effects of vibration in ovo reminiscent of transportation at day E1 have shown that vibrations during early embryogenesis (Donofre et al, 2017) or chronically between day E0 and day E15 (Shannon et al, 1994) can reduce the percentage of chicks hatching. Exposure to sound in ovo may also affect chick development, possibly to the benefit of hatchability in some cases of chronic sound exposure continuously throughout incubation (Donofre et al, 2020) but with long-term effects on behaviour seen in quail following chronic noise exposure in ovo (Mezrai et al, 2022). The auditory system in chicks is developed and responsive to a mature hearing range by day E16-E18 (Jones et al, 2006), making it likely that embryos can respond to transportation noise at day E18 as well.…”
Section: Introductionmentioning
confidence: 99%